2021
DOI: 10.1186/s12302-021-00528-5
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of microbial populations in plastic–soil systems after exposure to high poly(butylene succinate-co-adipate) load using high-resolution molecular technique

Abstract: Background Bio-based and biodegradable plastics are considered as plastics of the future owing to their ability to decompose under various environmental conditions. However, their effects on the soil microbiome are poorly characterised. In this study, we aimed to investigate the effects of an important bio-based and biodegradable plastic, polybutylene succinate-co-adipate (PBSA), on soil microbial diversity and community composition using high-resolution molecular technique (Illumina sequencing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 74 publications
0
29
0
Order By: Relevance
“…To demonstrate that N fixation is the rate-limiting step in PBSA degradation in soil, we set-up a PBSA laboratory decomposition experiment using the soil from the GCEF experimental plot as described in our previous study. 32 Briefly, PBSA films were treated with 70% ethanol to sterilize their surfaces and cut into pieces (2–5 mm × 2–5 mm). These pieces (1 g or 6% PBSA, w/w) were buried in sterile glass jars containing 15.7 g dry soil equivalent from one of the two following treatments: (i) soil (PBSA-soil; PS treatment) and (ii) soil with N addition (PBSA-soil-N; PSN treatment), with five independent replicates.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…To demonstrate that N fixation is the rate-limiting step in PBSA degradation in soil, we set-up a PBSA laboratory decomposition experiment using the soil from the GCEF experimental plot as described in our previous study. 32 Briefly, PBSA films were treated with 70% ethanol to sterilize their surfaces and cut into pieces (2–5 mm × 2–5 mm). These pieces (1 g or 6% PBSA, w/w) were buried in sterile glass jars containing 15.7 g dry soil equivalent from one of the two following treatments: (i) soil (PBSA-soil; PS treatment) and (ii) soil with N addition (PBSA-soil-N; PSN treatment), with five independent replicates.…”
Section: Methodsmentioning
confidence: 99%
“…These pieces (1 g or 6% PBSA, w/w) were buried in sterile glass jars containing 15.7 g dry soil equivalent from one of the two following treatments: (i) soil (PBSA-soil; PS treatment) and (ii) soil with N addition (PBSA-soil-N; PSN treatment), with five independent replicates. In the PSN treatment, the soil was supplemented with the same amount of N (1.4 mL of 1.42 M (NH 4 ) 2 SO 4 , equivalent to 0.055 g N per jar or 280 kg N per hectare which is comparable to the highest rate of N fertilisation used in agroecosystems) 32 that is usually present in the initial soil without PBSA. Soils without PBSA (with and without N amendment, 16.7 g) were used as controls.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Qi et al, found that biodegradable films had a stronger effect on the rhizosphere microbial community than low-density PE (LDPE) and biodegradable films had higher relative abundances of certain bacterial genera including Bacillus , Variovorax and Comamonadaceae [54] . Tanunchai et al, found that adding a biodegradable plastic poly-butylene succinate-co-adipate (PBSA) to soil, microbial communities significantly changed microbial community composition and that archaeal and fungal species richness declined [57] .…”
Section: Characterization Of Pamcs or The Plastispherementioning
confidence: 99%